Mesenchymal Stromal Cells Affect Disease Outcomes via Macrophage Polarization - Guoping Zheng; Menghua Ge; Guanguan Qiu; Qiang Shu; Jianguo Xu (Stem Cells International)
Mesenchymal stromal cells (MSCs) are multipotent and self-renewable cells that reside in almost all postnatal tissues. In recent years, many studies have reported the effect of MSCs on the innate and adaptive immune systems. MSCs regulate the proliferation, activation, and effector function of T lymphocytes, professional antigen presenting cells (dendritic cells, macrophages, and B lymphocytes), and NK cells via direct cell-to-cell contact or production of soluble factors including indoleamine 2,3-dioxygenase, prostaglandin E2, tumor necrosis factor-α stimulated gene/protein 6, nitric oxide, and IL-10. MSCs are also able to reprogram macrophages from a proinflammatory M1 phenotype toward an anti-inflammatory M2 phenotype capable of regulating immune response. Because of their capacity for differentiation and immunomodulation, MSCs have been used in many preclinical and clinical studies as possible new therapeutic agents for the treatment of autoimmune, degenerative, and inflammatory diseases. In this review, we discuss the central role of MSCs in macrophage polarization and outcomes of diseases such as wound healing, brain/spinal cord injuries, and diseases of heart, lung, and kidney in animal models.